2022
DOI: 10.22541/au.166831755.54665841/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring and Analysis of Ground Subsidence in Shanghai Based on PS-InSAR and SBAS-InSAR Technologies

Abstract: To monitor the ground sink condition of Shanghai over the past two years, monitoring data were obtained through the technical processing of 24 views from Sentinel-1A data covering Shanghai from 2019–2020 by using the PS-InSAR and SBAS-InSAR technique. The ground subsidence results were extracted via PS interferometry processing, while SRTM data were used to correct the residual phase. The subsidence rate and the accumulated amount of subsidence derived from the monitoring results revealed the urban area in Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…With the ability to detect displacements at the millimeter level and derive surface deformation rates from multi-temporal data, PS-InSAR proved valuable for urban management and decision-making (Zhang et al 2023b). In summary, PS-InSAR technology provided a powerful tool for monitoring urban surface deformation, enabling precise measurements and e cient analysis of subsidence rates over time (Zhang et al 2023c).…”
Section: Ps-insar Technique For Ground Subsidence Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the ability to detect displacements at the millimeter level and derive surface deformation rates from multi-temporal data, PS-InSAR proved valuable for urban management and decision-making (Zhang et al 2023b). In summary, PS-InSAR technology provided a powerful tool for monitoring urban surface deformation, enabling precise measurements and e cient analysis of subsidence rates over time (Zhang et al 2023c).…”
Section: Ps-insar Technique For Ground Subsidence Detectionmentioning
confidence: 99%
“…Traditional measurement techniques, such as GPS, leveling, and microgravity surveys, have been employed to monitor ground deformation. However, these methods are often limited by high costs, timeconsuming processes, and restricted spatial coverage, rendering them inadequate for large-scale, highprecision ground deformation monitoring (Zhang et al 2023b; Zhang et al 2023c). In contrast, satellite Interferometric Synthetic Aperture Radar (InSAR) technology has emerged as a powerful tool for monitoring ground deformation, offering advantages of all-weather operation, extensive area coverage, high accuracy, and low cost (Cigna et al 2021;Du et al 2021;Liu and Zhang 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This study provided a feasible approach for utilizing InSAR subsidence constraints to invert the parameters of fully-mechanized coal mining faces. Additionally, the relationship between the parameters of fully-mechanized mining faces and the coal seam apparent density was established, offering a valuable strategy for combining the parameters of mining faces with extraction quantities; Yujie Han et al [3] processed a total of 36 scenes of Sentinel-1A data from July 2015 to December 2017 in a mining area in Shandong using a combination of PS-InSAR and SBAS techniques. They obtained the average displacement rate and temporal position series in the study area and found that the ground subsidence information obtained through SBAS technology had higher accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…As rapid urbanization surges forth, ground subsidence emerges as a geohazard impeding urban development and coalescence, as evident in cities like Mexico City (Fernández-Torres et al 2023) and Italy (Zuccarini et al 2024). China has experienced extensive urban ground subsidence in several areas such as Luoyang, Yan'an and Shanghai (Zhang et al 2022;Zhang et al 2023;Zhao et al 2023). In urban settings, ground subsidence can precipitate foundation failures, damage subterranean pipelines, and wreak havoc on road networks (Shi et al 2021).…”
Section: Introductionmentioning
confidence: 99%